2005
DOI: 10.1021/ac0505730
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Optic Probes for in Vivo Raman Spectroscopy in the High-Wavenumber Region

Abstract: In vivo Raman spectroscopy, using fiber-optic probes is hindered by the intense background signal, which is generated in the fused-silica fibers, in the fingerprint region of the Raman spectrum (approximately 0-2000 cm(-1)). Optical filtering is necessary to obtain tissue spectra of sufficient quality. The complexity of fiber-optic probes for fingerprint Raman spectroscopy, in combination with size constraints and flexibility requirements for in vivo use have been a major obstacle in the development of in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 19 publications
4
112
0
1
Order By: Relevance
“…This avoids the glass signal existing primarily in the fingerprint region (600-1800 cm −1 ) [124]. They found that the Raman signal from the high wavenumber region contained similar information and could create similar hyperspectral images to those from specta in the fingerprint region [436].…”
Section: Challengesmentioning
confidence: 99%
“…This avoids the glass signal existing primarily in the fingerprint region (600-1800 cm −1 ) [124]. They found that the Raman signal from the high wavenumber region contained similar information and could create similar hyperspectral images to those from specta in the fingerprint region [436].…”
Section: Challengesmentioning
confidence: 99%
“…2). Confounding Raman signals arising from the probe fiber usually preclude using a single fiber for Raman endoscopy in this wave number range (16)(17)(18), but in our case, these obstructing signals are out of resonance and/or out of the analysis window and thus cause no interference. The isolated 1,525 cm −1 C=C resonance Raman carotenoid peak is further characterized using a Lorentzian line shape, and the peak attributes are reported.…”
Section: Methodsmentioning
confidence: 83%
“…Investigative groups are exploring the use of a single fiberoptic mode of delivering and collecting Raman measurements (16)(17)(18), but systems that monitor a broad bandwidth are easily overwhelmed by background fluorescence obscuring relatively weak Raman signals. Our single-fiber resonance-enhanced Raman system able to provide both illumination and collection is made possible by the relative ease by which our software and optics can eliminate background fluorescence within a relatively narrow bandwidth of interest for carotenoids.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas RS in vivo cancer detection has been exploited, Raman spectroscopy although is not a novel technology but its application for cancer detection is a new scope  and recent advances in RS have promoted it to a level at which in vivo trials are beginning to emerge [1214] RS application as a histopathologic tool has been considered mostly now that it is often exploited for examination of biopsied tissues since they may contain very small amounts of material to be searched. Accordingly, among the numerous techniques based on Raman, SERS seems to be more capable of achieving this purpose [4,69].…”
Section: Cancer Detection Using Ramanmentioning
confidence: 99%
“…In recent investigations, Koljenovic et al [84] used a fiber-optic Raman probe with high wave number of laser beams (2400–3800 cm −1 ) to characterize brain tissue of a pig ex vivo . Raman spectra of the gray matter were characterized by high intensity band related to nucleic acids, proteins and phosphatidyl choline while the spectra of the white matter were associated with cholesterol, galactocerebroside and sphingomyeline [14]. Aydin et al demonstrated the usefulness of SERS to differentiate healthy brain tissues from malignant ones.…”
Section: Brain Cancermentioning
confidence: 99%